Non-native memory traces can be further strengthened by short term phonetic training - Henna Tamminen; Maija S. Peltola (United Kingdom, 2022)
Learners of a second language go through many proficiency levels during language learning. University language students can be considered advanced learners, who behaviourally perceive the language at least nearly similarly as native speakers. It can also be assumed that memory traces for the second language phonemes have developed for these learners and their MMN responses for foreign contrasts may be even native-like. Here, we wanted to find out, whether these students have memory traces for second language speech categories. Further, we investigated whether their behavioural perception can be improved and can the memory traces be strengthened by training. For this purpose we tested Finnish university students of English on a three-day listen-and-repeat training procedure. The baseline MMN response was further strengthened and category boundary became more consistent, reaction times decreased and discrimination sensitivity increased. The perception – behavioural and psychophysical – of the learners of English was further strengthened by listen-and-repeat training.
18th International Congresses of Phonetic Sciences